2011
DOI: 10.1001/archgenpsychiatry.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Addictive Disorders in a First-Offender Driving While Impaired Population

Abstract: Context We compared the prevalence of alcohol use and other psychiatric disorders in offenders 15 years after a first conviction for driving while impaired with a general population sample. Objective To determine whether high rates of addictive and other psychiatric disorders previously demonstrated in this sample remain disproportionately higher compared with a matched general population sample. Design Point-in-time cohort study. Setting Pacific Institute for Research and Evaluation, Albuquerque, New Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
(33 reference statements)
2
19
0
Order By: Relevance
“…Methodologically, the lower treatment completion rate in the contingent condition, relative to the non-contingent condition, resulted in group differences in rates of missing data. However, we utilized robust statistical methods (i.e., multiple imputation), that have been frequently used in psychiatric research where comparable levels of missing data were observed (34, 35), to account for missing data (see the Data Analysis section) and conducted multiple sensitivity analyses to corroborate the findings of our multiple imputation approach. Despite these consistent results, it is important to note that all imputation strategies bias study results, with some (e.g., single imputation) introducing more bias than others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologically, the lower treatment completion rate in the contingent condition, relative to the non-contingent condition, resulted in group differences in rates of missing data. However, we utilized robust statistical methods (i.e., multiple imputation), that have been frequently used in psychiatric research where comparable levels of missing data were observed (34, 35), to account for missing data (see the Data Analysis section) and conducted multiple sensitivity analyses to corroborate the findings of our multiple imputation approach. Despite these consistent results, it is important to note that all imputation strategies bias study results, with some (e.g., single imputation) introducing more bias than others.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has significant advantages over single imputation or listwise deletion (31) or other techniques (32, 33) in conjunction generalized estimation equation analyses and has frequently been used in psychiatric studies with similar levels of missing data (34, 35). Multiple imputations requires the assumption of ‘missing at random.’ This method of is a more conservative approach compared to the default listwise deletion used in generalized estimation equations analyses which assumes ‘missing completely at random.’ Preliminary analyses identified 12 variables that predicted missingness due to treatment dropout.…”
Section: Methodsmentioning
confidence: 99%
“…The Structured Clinical Interview for DSM-IV – Axis I (SCID; First, Spitzer, Gibbon, & Williams, 1998) was used to identify Axis I DSM-IV disorders other than PTSD and to determine whether potential participants met exclusion for a psychotic disorder. The antisocial and borderline personality disorder modules of the SCID – Axis II (First, Spitzer, Gibbon, & Williams, 1997) assessed the most common personality disorders in people with chronic SUD and PTSD (Friborg, Martinussen, Kaiser, Overgård, & Rosenvinge, 2013; Hasin et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…1,2 Like other chronic illnesses (e.g., diabetes, hypertension), alcohol use disorders (AUDs) have both physiological and behavioral components. AUDs also have relapse rates similar to those of other chronic illnesses.…”
mentioning
confidence: 99%